DESIGN AND DEVELOPMENT OF A LARAVEL-BASED ACADEMIC GRADING SYSTEM AT PIKSI GANESHA POLYTECHNIC - Seliwati, Seliwati; Nugroho, Alpin Agung (Bakti Nusantara Institute, 2025)
This research aims to design and develop a web-based student grading information system using the Laravel framework within Piksi Ganesha Polytechnic. The system is developed to facilitate lecturers in inputting student grades according to the deadlines set by the academic department. The development method applied is the Waterfall model, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. System testing was carried out using the black-box testing method to ensure that each feature functions as intended. The results showed that this system is capable of assisting lecturers in assessing students in a more structured and timely manner. The main features developed include grade input, input deadline settings, automatic notifications when only three days remain, forms that are automatically disabled once the deadline passes, and a progress bar to help lecturers monitor grade input completion for each class. Based on the trial results, the system received positive responses from users as it enhances efficiency and discipline in the grading process. The implementation of this grading information system is expected to support academic management in a more effective, transparent, and accountable manner, as well as become a relevant technological innovation to promote digital transformation at Piksi Ganesha Polytechnic, thereby improving the quality of integrated and sustainable academic services.